2013
DOI: 10.3136/fstr.19.445
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Quality Loss in Wild and Cultured Rainbow Trout (Oncorhynchus mykiss) during Chilling Storage

Abstract: The aim of this study was to determine and compare differences in sensory, chemical and microbiological post-mortem changes between wild and farmed rainbow trout (Oncorhynchus mykiss). Lipid content was higher (5.77%) in wild fish than cultured fish (3.02%). Wild fish were very rich in n-3 fatty acids. Although wild fish were preferred to cultured fish due to the taste and flavour, shelf life of both wild and cultured rainbow trout was 14 days with demerit scores of 16 and 14, respectively. Chemical analyses s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Wunnenberg and Oehlenscläger [33] reported the shelf life of rainbow trout that are stored on ice on autumn for 14 days and on winter, spring, and summer for 16 days. Ninan et al [34] found the shelf life of whole rainbow trout in accordance with the sensory results for 12-14 days while Özoğul et al [35] found similar shelf life, namely, 14 days for whole wild and aquacultered rainbow trout. In addition, Chytiri et al [36] reported 15-16 days in whole rainbow trout on ice and 10-12 days shelf life for fillet.…”
Section: Discussionmentioning
confidence: 56%
“…Wunnenberg and Oehlenscläger [33] reported the shelf life of rainbow trout that are stored on ice on autumn for 14 days and on winter, spring, and summer for 16 days. Ninan et al [34] found the shelf life of whole rainbow trout in accordance with the sensory results for 12-14 days while Özoğul et al [35] found similar shelf life, namely, 14 days for whole wild and aquacultered rainbow trout. In addition, Chytiri et al [36] reported 15-16 days in whole rainbow trout on ice and 10-12 days shelf life for fillet.…”
Section: Discussionmentioning
confidence: 56%
“…In cultured fish, the ω3 PUFA is generally lower than that of wild fish because of possibly the lack of lipids originating from phytoplankton and aquatic organisms in cultured diets (Ackman & Takeuchi, 1986). Similarly, Ozogul et al (2013) stated that wild fish had much higher ω3 fatty acids than their cultured ones. This situation could result from the feed.…”
Section: Resultsmentioning
confidence: 99%
“…Another important factor affecting fatty acid composition is whether the fish is wild or cultured. Wild fish contain more ω3 fatty acids than cultured fish (Ozogul, Yavuzer, Ozogul, & Kuley, 2013). In addition, wild fish living in lakes are better sources of DHA than cultured fish reared in polyculture (Łuczyńska, Tońska, Krejszeff, & Żarski, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Without using the internal preference map approach, Pohar (2011) observed that the panel created by his team had a slight preference for farmed brown trout. Ozogul et al (2013) verified that consumers preferred wild rainbow trout. These discrepancies found among different research results might be related with both with fish intrinsic and extrinsic features (geographical origin, genotype, season, sexual maturation, age, feeding, water quality, presence of disease and parasites), which influence fish chemical composition and, consequently, fish sensory variables (taste, texture, and appearance) which, in turn, determine fish quality, consumer acceptance and commercialization (Grigorakis, 2007;Green-Petersen & Hyldig, 2010;Oken et al, 2012;Claret et al, 2014;Suomela et al, 2016).…”
Section: Sensory Acceptability Of the Fish Samplesmentioning
confidence: 81%